Measures to support students' research activities and scientific mentoring in Russian universities - P. A. Ambarova; N. V. Shabrova (Moscow Polytechnic University, 2024)
The present paper is devoted to the search for successful experience and analysis of the problems of supporting students' research work (R&D) and scientific mentoring in Russian universities.   The relevance of the topic is due to the need to evaluate approaches to stimulating not only research and development, but also the activities of scientific mentors in terms of the sustainability and effectiveness of the impact of existing support measures on student involvement in science andteachers' motivation to mentoring activities.   Since the interaction of students and scientific mentors, implemented in the unique organizational conditions of each particular university, and a typical all-Russian context, forms an ecosystem, the article focuses on considering measures to support research and scientific mentoring in interrelation.   The purpose of the article is to consider measures to support research and scientific mentoring in Russian universities.   The results of an empirical study conducted in 2024 using the methods of traditional analysis of documents (normative legal acts on measures to support research and development at the federal, regional and local levels) and a semi-structured interview with scientific mentors from among academic staff of universities (n = 30) are presented.   Main results: generalization of measures to support research and development at three levels (federal, regional and local) of higher education management. It is shown that, at the federal level, they are worded extremely broadly, allowing the regions and universities to specify and refine them.The uneven distribution of support measures by region and their emphasis on financial incentives are revealed. It is concluded that each university has a limited number of documents regulating the support of research and mentoring. The contradictions in the attitude of the academic staff to the measures of support for research and scientific mentoring were disclosed. The prospects for the development of a research programme to support research and scientific mentoring in universities are considered.